Economia Criativa: uma análise dos rendimentos da Indústria Criativa nos Estados brasileiros - Rodrigues, Sara Marinho (Brasil, 2024)
Creative Economy and Creative Industry are relatively new concepts that have stood out in recent decades among public policy makers who sought an alternative to promote the growth and competitiveness of their economies. Considering the importance that this economy has assumed in recent years, the research sought to analyze the incomes of the creative industry compared to the incomes of traditional industry and which regions of Brazil offer the best wages. For this, we estimated a regression based on the Mincerian income equation with the traditional variables of the equation such as education, experience, as well as variables about the creative industry and binary variables of region, male and female, and race. It was found that workers inserted in the Creative Industry tend to have a higher hourly wage than workers in the economy in general. While the South, Midwest and Southeast regions of Brazil offer the best salaries.